2021
DOI: 10.1007/s10792-021-02129-w
|View full text |Cite
|
Sign up to set email alerts
|

Retinal optical coherence tomography angiography findings of acute anterior uveitis

Abstract: Purpose: To evaluate the changes in retinal microvasculature in eyes with anterior uveitis (AU) using optical coherence tomography angiography.Methods: Foveal avascular zone (FAZ) of super cial capillary plexus (SCP) and deep capillary plexus (DCP), vessel density (VD) of SCP, DCP, and choriocapillaris, and central macular thickness (CMT) and central foveal thickness (CFT) were calculated from 34 healthy and 41 uveitic eyes. The parameters were compared between the two groups.Results: The deep FAZ was signi ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…With OCT-A, an increase in vascular density was demonstrated in both the superficial and deep capillary plexus during the active phase of AAU, as well as a decrease in the area of the deep foveal avascular zone, although these changes resolved after the inflammation regressed. These studies emphasize the fact that regardless of anatomical location, uveitis can lead to microvascular changes [21]. Similarly, such changes can develop in the peripapillary area that features numerous vessels covering the entire retina.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…With OCT-A, an increase in vascular density was demonstrated in both the superficial and deep capillary plexus during the active phase of AAU, as well as a decrease in the area of the deep foveal avascular zone, although these changes resolved after the inflammation regressed. These studies emphasize the fact that regardless of anatomical location, uveitis can lead to microvascular changes [21]. Similarly, such changes can develop in the peripapillary area that features numerous vessels covering the entire retina.…”
Section: Discussionmentioning
confidence: 68%
“…The use of enhanced depth imaging OCT (EDI-OCT) has shown that choroidal thickness increases during the active phase of the disease and then decreases in response to treatment [18,20]. Using OCT angiography (OCT-A), it is noted that inflammation involving the anterior segment of the eye also affects the macular microvasculature [21]. Pre-existing research regarding the pRNFL likewise indicates that the thickness of the pRNFL increases, but these analyses have included adults with different AAU etiologies, and the control group has often consisted of the other eye of the same patient [18,22,23].…”
Section: Introductionmentioning
confidence: 99%